(3YLGFH GdeNdhbGJ hZQGFH GdehLhOGJs - (3RcQjG Hf eMeO Hf eMehO,GdnbrRphjfj, CHh jMji YeGO GdOjf,J (B682 (3g` s
(3ChdgG (B:s
(3Gddge Udi Ydi SjOfG eMeO jbhd GdbRhjfi QMeg Gddg Cfg deG bVi Gddg JYGdi Ydi HHYO GdOGQ hGdhWf GbHdJ Ydi eWGdYI GdcJH s
(3BNQgG (B:s
(3BNQ GdehLhO efg hbdg (B:(3R GdbSe GdKGdK MjhGfGJ ZQjHI GdUhJ hRYe GdefLehf Gf ebJVi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B183s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1127s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdcjejGA h GdWHjYjGJs